Association between hsa-miR-34b/c rs4938723 T > C promoter polymorphism and cancer risk: a meta-analysis based on 6,036 cases and 6,204 controls - Tao, Tao; Chen, Shuqiu; Xu, Bin; Liu, Chunhui; Wang, Yiduo; Huang, Yeqing; Chen, Ming (Chinese Journal of Cancer Research; Vol 26, No 3 (June 01, 2014): Chinese Journal of Cancer Research, 2014)
Objective: Emerging evidence shows that microRNAs (miRNAs) function as tumor suppressors or oncogenes in human carcinogenesis. A single nucleotide polymorphism (SNP) located in the pri-miRNA promoter may affect the processing and expression of mature miRNA. However, previous studies showed conflicting results regarding the association of hsa-miR-34b/c rs4938723 T > C promoter polymorphism with cancer. Therefore, we conducted a meta-analysis to determine the association of polymorphism with cancer risk. Methods: A computerized search of PubMed, Web of Science, and Chinese National Knowledge Infrastructure (CNKI) for publications on hsa-miR-34b/c rs4938723 T > C promoter polymorphism and cancer risk was performed and the genotype data were analyzed in a meta-analysis. Odds ratios (ORs) with 95% confidence intervals (CIs) were estimated to assess the association. Test of heterogeneity, cumulative meta-analysis, sensitivity analysis and assessment of bias were performed in our meta-analysis by STATA software 12.0. Results: There was no significant association between hsa-miR-34b/c rs4938723 polymorphism and overall cancer risk in the comparison models. Moreover, subgroup analysis revealed that the variant CT (OR =1.19, 95% CI: 1.03-1.37) and CC/CT (OR =1.18, 95% CI: 1.03-2.35) genotypes were associated with an increased risk of hepatocellular carcinoma (HCC) compared with wild-type TT genotype. However, a decreased risk of colorectal cancer (CRC) was found in the genetic model of CC/TT (OR =0.66, 95% CI: 0.47-0.92) and CC/CTTT (OR =0.67, 95% CI: 0.49-0.93). Conclusions: The results suggest that hsa-miR-34b/c rs4938723 polymorphism may play an opposite role in different types of cancer based on current studies, which is the main origin of heterogeneity in this meta-analysis. Further large-scale studies and functional studies between this polymorphism and cancer risk are warranted.